The Effect of Job Resources on Work Engagement through Job Crafting and Burnout in Public High School Teachers in West Kotawaringin - Yenni Lawrensia; Tuty Lindawati (Publikasi Indonesia, 2024)
This study aims to determine the effect of job resources on work engagement through job crafting and burnout in public high school teachers in West Kotawaringin. This study is a causal study. The data collection tool used is an online questionnaire in the form of a google form. Questionnaires are distributed by snowball sampling, where some subjects will be selected to represent the school and then distribute the questionnaire to others. The population in this study is public high school teachers in West Kotawaringin. The sample in this study was 166 respondents with the criteria of having worked as teachers for one year. Data analysis techniques in this study use SEM (Structural Equation Model) using the lisrel program. The results showed that there is a positive and significant influence between job resources on work engagement, there is a positive and significant influence between job resources on job crafting, there is a negative influence between job resources on burnout, there is no positive and significant influence between job crafting on work engagement, there is a negative influence between burnout on work engagement, there is a positive and significant influence between job resources on work engagement through job crafting, and there is a positive and significant influence between job resources on work engagement through burnout.